2018
DOI: 10.1080/17429145.2018.1472307
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere mediated nutrient management inAllium hookeriThwaites by using phosphate solubilizing rhizobacteria and tricalcium phosphate amended soil

Abstract: This work describes integrated nutrient management for cultivation of Allium hookeri by using phosphate solubilizing bacteria (PSB) applied in rhizosphere, along with tricalcium phosphate (TCP). Arthrobacter luteolus S4C7, Enterobacter asburiae S5C7, Klebsiella pneumoniae S4C9, S4C10 and S6C1, and K. quasipneumoniae S6C2, were isolated from rhizosphere of Allium hookeri Thwaites, and were found to release substantial amount of soluble phosphate (124.8-266.4 μg/mL) from TCP in vitro conditions. These isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 75 publications
2
5
0
Order By: Relevance
“…Table 5 shows the phosphate solubilization values obtained from Pseudomonas bacteria isolated from the rhizospheric soil of coffee plants, according to the CCD matrix, with corresponding process variables. Solubility of phosphate obtained in this experiment was found to be in the range of 125.67 µg/ml -270.12 µg/ml (Table 5), which is comparable to the phosphate solubilizing bacteria (PSB) isolated from the rhizosphere of Allium hookeri Thwaites (124.8-266.4 μg/mL) [39] and higher than phosphate solubilizing bacteria (PSB) isolated from rhizobacterial salinized soils (44.00 -63.90 mg/L) [38]. In the present work, the higher solubility of phosphate suggests that bacterial strain increases the soluble phosphate content of the soil, thereby improving phosphate absorption.…”
Section: Effect Of Process Variables On the Phosphate Solubilizationsupporting
confidence: 63%
See 2 more Smart Citations
“…Table 5 shows the phosphate solubilization values obtained from Pseudomonas bacteria isolated from the rhizospheric soil of coffee plants, according to the CCD matrix, with corresponding process variables. Solubility of phosphate obtained in this experiment was found to be in the range of 125.67 µg/ml -270.12 µg/ml (Table 5), which is comparable to the phosphate solubilizing bacteria (PSB) isolated from the rhizosphere of Allium hookeri Thwaites (124.8-266.4 μg/mL) [39] and higher than phosphate solubilizing bacteria (PSB) isolated from rhizobacterial salinized soils (44.00 -63.90 mg/L) [38]. In the present work, the higher solubility of phosphate suggests that bacterial strain increases the soluble phosphate content of the soil, thereby improving phosphate absorption.…”
Section: Effect Of Process Variables On the Phosphate Solubilizationsupporting
confidence: 63%
“…Production of IAA was slightly lower than IAA produced by the cultures growing the isolates in YEM broth amended with 0.2 % of L-tryptophan (52.9-186.65 μg/mL) [39]. IAA production is an indicator of plant growthpromoting rhizobacteria.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this study, three isolates identified as Klebsiella quasipneumoniae and one as Klebsiella pneumonia were isolated from bulk soil and rhizosphere samples of tomato plants grown on peat moss and clay. K. quasipneumoniae can improve plant growth via the solubilization of inorganic phosphate [ 57 ]. However, it has the ability to adapt to both plant and clinical environments [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biofertilizers are gaining importance as they are eco-friendly, non-hazardous and non-toxic products (Gichimu, Muthee and Nthakanio, 2020). They can also reduce and solve environmental problems related to abiotic factors such as temperature, pH and salt (Kshetri, Pandey and Sharma, 2018).…”
Section: Introductionmentioning
confidence: 99%